2012
DOI: 10.7475/kjan.2012.24.4.370
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Depression of Married Immigrant Women in Rural Areas

Abstract: Purpose: This study aimed to identify factors influencing depression of married immigrant women in rural areas. Methods: The participants were 206 married immigrant women in Jeollanamdo, Korea. The data were collected using a structured questionnaire from November to December 2011 and analyzed using descriptive statistics, one-way ANOVA, Scheffé test, Pearson correlation coefficient, and stepwise multiple regression with SPSS/WIN 18.0. Results: The participants' mean age was 28.3 (range=20 to 49). Depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…However, in a recent cross-sectional study of investigating mental health status of 173 migrant women residing in South Korea, Kim and Kim ( 2013 ) found that almost 1 in 10 (9.7 %) participants reported depressive symptoms, a rate that was two to threefold higher than that of general Korean population (2.9-5.6 %) ). Moreover, the previous studies that were conducted in various provinces in South Korea showed that approximately 15-45 % of migrant women reported mild state of depression (Jeong, Kim, & Bae, 2012 ;Kim & Jung, 2011 ;Roh & Kim, 2012 ). These fi ndings are consistent with other previous studies that were conducted with the U.S. community samples, which found higher levels of depressive symptoms among Korean-Americans who resided in America (Oh et al, 2002 ).…”
Section: Mental Health Issues In International Marriage Migrant Womensupporting
confidence: 89%
“…However, in a recent cross-sectional study of investigating mental health status of 173 migrant women residing in South Korea, Kim and Kim ( 2013 ) found that almost 1 in 10 (9.7 %) participants reported depressive symptoms, a rate that was two to threefold higher than that of general Korean population (2.9-5.6 %) ). Moreover, the previous studies that were conducted in various provinces in South Korea showed that approximately 15-45 % of migrant women reported mild state of depression (Jeong, Kim, & Bae, 2012 ;Kim & Jung, 2011 ;Roh & Kim, 2012 ). These fi ndings are consistent with other previous studies that were conducted with the U.S. community samples, which found higher levels of depressive symptoms among Korean-Americans who resided in America (Oh et al, 2002 ).…”
Section: Mental Health Issues In International Marriage Migrant Womensupporting
confidence: 89%
“…Empirically, many researchers have reported the high prevalence of depression in married immigrant women. Roh and Kim (2012), for example, examined the prevalence of depression among 206 married immigrant women living in Jeonnam province and found that 52.9% of the participants were at risk of clinical depression (using a cut-off score of 16) and 22.8% had depression (using scores over 25). Of the 316 female married immigrants who participated in Kim et al's (Kim, Yang, Chee, Kwon & An, 2015) study, 39.9% were at risk of clinical depression.…”
Section: Introductionmentioning
confidence: 99%
“…However, older women reported higher levels of depression than younger women (Cha & Kim, ). Further, there was no statistical association between age and depression among marriage‐based migrant women living in agricultural areas (Choi & Yoon, ; Roh & Kim, ). The length of stay in Korea also indicated mixed results, with Park () reporting a positive relationship, while Lim () showed the opposite.…”
Section: Literature Reviewmentioning
confidence: 99%